2003
DOI: 10.1021/ef020119o
|View full text |Cite
|
Sign up to set email alerts
|

Alkane Adsorption on Microporous SiO2 Substrata. 1. Textural Characterization and Equilibrium

Abstract: Microporous silica solids of SiO 2 and Ag/SiO 2 (a microporous SiO 2 substrate containing 5 wt % Ag) are synthesized by the sol-gel method and analyzed through several characterization techniques. The type I shapes of N 2 sorption isotherms at 76 K on these materials indicate large micropore contents as well as important cohesive interactions between adsorbed N 2 molecules, i.e., a gradual cooperative filling process becomes more and more evident as the concentration of adsorbate within the porous structure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Volatile organic compounds (VOCs) are a class of air pollutants in industrial processes and daily human consumption Parmar and Rao, 2009;He et al, 2012;Hernandez et al, 2003;Ghoshal and Manjare, 2002;Reguer et al, 2011;Gonzalez-Miquel et al, 2013). Because of their high vapor pressure and low boiling point, they are prone to be emitted into the atmosphere, causing great environmental problems because of their intrinsically hazardous properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Volatile organic compounds (VOCs) are a class of air pollutants in industrial processes and daily human consumption Parmar and Rao, 2009;He et al, 2012;Hernandez et al, 2003;Ghoshal and Manjare, 2002;Reguer et al, 2011;Gonzalez-Miquel et al, 2013). Because of their high vapor pressure and low boiling point, they are prone to be emitted into the atmosphere, causing great environmental problems because of their intrinsically hazardous properties.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high vapor pressure and low boiling point, they are prone to be emitted into the atmosphere, causing great environmental problems because of their intrinsically hazardous properties. Not only they are the main precursors of photochemical reaction in the atmosphere, inducing ozone destruction and photochemical smog, but they are also toxic toward human health, and may cause pathogenic, mutagenic and even fatal diseases (Wang et al, 2007;Parmar and Rao, 2009;He et al, 2012;Hernandez et al, 2003). Unfortunately, with the continuous development of industrialization in recent years, the emissions of VOCs have gradually increased to a new high level (Ghoshal and Manjare, 2002;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yun et al 12 reported the adsorption of the C 1 and C 2 alkanes, and their binary mixtures on hexagonally ordered MCM-41, and validated methods for the prediction of adsorption equilibrium. Hernandez et al 13 measured the adsorption capacities of the linear C 6 ,C 7 ,C 8 , and C 9 alkanes on microporous silica solids at different temperatures, and found the limiting adsorption energy to be more attractive for a longer alkane.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yuan et al 20 studied the adsorption and separation properties of CO 2 , N 2 , and CH 4 on OMC. The results revealed that OMC has high adsorption capacities for CO 2 and CH 4 and high selectivities for CO 2 /CH 4 , CH 4 /N 2 , and CO 2 /N 2 mixtures simultaneously. All of the relevant research results confirm the superior adsorption properties of OMCs.…”
Section: Introductionmentioning
confidence: 98%